The Ability of Bacteriophages to Reduce Biofilms Produced by Pseudomonas aeruginosa Isolated from Corneal Infections - Kuma Diriba Urgeya; Dinesh Subedi; Naresh Kumar; Mark Willcox (Antibiotics)
Pseudomonas aeruginosa (P. aeruginosa) is a common antibiotic-resistant pathogen, posing significant public health threats worldwide. It is a major cause of ocular infections, mostly linked to contact lens wear. P. aeruginosa often produces biofilm during infections, and these are also associated with antibiotic resistance. Bacteriophage (phage) therapy is emerging as a promising approach for treating multidrug-resistant P. aeruginosa. Objective: This study aimed to assess the antibiofilm effects of six phages against P. aeruginosa biofilms isolated from patients with corneal infections. Method: This study examined P. aeruginosa strains for their ability to form biofilms using crystal violet assay. Six P. aeruginosa bacteriophages (DiSu1 to DiSu6) were used, which were isolated from sewage water in Melbourne, Australia. Spot tests were used to assess phage sensitivity. The effect of phages against P. aeruginosa strains was determined using time–kill assay and efficiency of plating. The ability of phage to inhibit biofilm formation over 24 h or reduce preformed biofilms was also studied and confirmed using confocal laser scanning microscopy with Live/Dead staining. Result: After 24 h of incubation, all tested P. aeruginosa strains formed moderate to strong biofilms. All P. aeruginosa strains were sensitive to at least four of the six phages. The highest level of bacterial growth inhibition in the liquid infection model was observed when phages were applied at a multiplicity of infection (MOI) of 100. Certain bacteria/phage combinations were able to inhibit biofilm formation over 24 h, with the combination of strain PA235 and phage DiSu3 producing the highest inhibition (83%) at a MOI of 100. This was followed by the combinations of PA223/DiSu3 (56%), and PA225/DiSu5 (52%). For the reduction in preformed biofilms, the best combinations were PA235 (90%), PA221 (61%), and PA213 and PA225 (57% each), all with DiSu3 after 3 h. However, exposing the biofilm with phages for over 24 h appeared to promote phage resistance as there was evidence of biofilm growth, with the only combination still showing a significant reduction being PA221/DiSu3 (58%) at MOI of 100. Conclusions: This study showed that the effect of phages against P. aeruginosa is concentration (MOI) dependent. Phages at higher MOI have the ability to disrupt, inhibit, and reduce P. aeruginosa biofilms. However, prolonged exposure of the biofilm with phages appeared to promote phage resistance. To enhance phage efficacy and address this form of resistance, further studies utilizing phage cocktails or a combination of phages and antibiotics is warranted.